Translating research into practice: the introduction of the INTERGROWTH‐21st package of clinical standards, tools and guidelines into policies, programmes and services. (9th September 2013) - Chatfield, A; Caglia, JM; Dhillon, S; Hirst, J; Cheikh Ismail, L; Abawi, K; Kac, G; Al Dhaheri, AS; Villar, J; Kennedy, S; Langer, A; ,
Abstract : The INTERGROWTH‐21 st Project has generated a package of international clinical standards, tools and guidelines. It is now necessary to plan for the next phase of the project: the translation of the research findings into practice through its global dissemination. The plan is to pre‐empt barriers to implementation by drawing from the published literature; gathering views and perspectives from policy makers, programmers and practitioners; incorporating input from local 'champions', and collecting and analysing data generated by a monitoring and evaluation system. Working at the global, regional, national and local levels will enable wide dissemination of the package, as well as increase the scope for adaptation and integration in diverse clinical contexts. We seek maximum uptake of the package in policies, guidelines and clinical practice to improve the quality of care offered to mothers and newborns. The strategy will also enhance our understanding of the effectiveness of different approaches to the translation of evidence into practice.